2018
DOI: 10.1080/14767058.2018.1499091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antenatal indomethacin on ductus arteriosus early closure and on adverse outcomes in preterm neonates

Abstract: The unexpected result shown by the multivariate analysis was the association between AI exposure and EDC (OR: 2.52, 95% CI: [1.02; 6.21]). This result, which has never been evidenced in previous studies, has great clinical importance. It is well known that PDA is more frequent at lower gestational ages, thus reducing the incidence of PDA could lead to an improvement of overall outcomes in extremely preterm newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Indomethacin has also been used postpartum for the drug treatment of patent ductus arteriosus (PDA), but there are no data on the effect of prenatal exposure on postpartum ductal patency. While Doni D primarily focused on the relationship between prenatal indomethacin (AI) and postnatal ductus arteriosus patency, it has been concluded that PDA is more common at low gestational age, thus reducing the incidence of PDA could improve overall outcomes in preterm neonates [ 1 ]. Inhaled nitric oxide (iNO) therapy is useful for the treatment of managed respiratory stress and acute episodes of hypoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…Indomethacin has also been used postpartum for the drug treatment of patent ductus arteriosus (PDA), but there are no data on the effect of prenatal exposure on postpartum ductal patency. While Doni D primarily focused on the relationship between prenatal indomethacin (AI) and postnatal ductus arteriosus patency, it has been concluded that PDA is more common at low gestational age, thus reducing the incidence of PDA could improve overall outcomes in preterm neonates [ 1 ]. Inhaled nitric oxide (iNO) therapy is useful for the treatment of managed respiratory stress and acute episodes of hypoxemia.…”
Section: Introductionmentioning
confidence: 99%